The Biodiversity–Biomass Relationship of Aquatic Macrophytes Is Regulated by Water Depth: A Case Study of a Shallow Mesotrophic Lake in China - Ma, Fei; Yang, Lei; Lv, Tian; Zuo, Zhenjun; Zhao, Haocun; Fan, Shufeng; Liu, Chunhua; Yu, Dan (Frontiers in Ecology and Evolution, 2021)
The relationship between biodiversity and productivity (or biomass production) (BPR) has been a popular topic in macroecology and debated for decades. However, this relationship is poorly understood in macrophyte communities, and the mechanism of BPR pattern of aquatic macrophyte community is not clear. We investigated 78 aquatic macrophyte communities in a shallow mesotrophic freshwater lake in the middle and lower reaches of the Yangtze River in China. We analysed the relationship between biodiversity (species richness, diversity and evenness indices) and community biomass and the effects of water environments and interspecific interactions on biodiversity-biomass pattern. Unimodal patterns between community biomass and diversity indices instead of evenness indices were shown, which indicating the importance of both the number and abundance of species when studying biodiversity-biomass pattern under mesotrophic conditions. These patterns were moderated by species identity biologically and water depth environmentally. However, water depth determined the distribution and growth of species with different lifeforms as well as species identities through environmental filtering. These results demonstrate that water depth regulates the biodiversity-biomass pattern of aquatic macrophyte community as a result of its effect on species identity and species distribution. Our study may provide useful information for conservation and restoration of macrophyte vegetation in shallow lakes through matching water depth and species or lifeforms combinations properly to reach high ecosystem functions and services.